Delineation of ocean surface provinces over a complex marine domain (off SW Iberia): an objective abiotic-based approach - Krug, Lilian (2018)
incorporating its dynamic nature. The area off Southwest Iberian Peninsula (SWIP), located between temperate and subtropical waters, includes oceanic and coastal domains affected by atmospheric and ocean circulation patterns, as well as coastal processes. The objectives of this study were to delineate a dynamic abiotic-based partition of the heterogeneous surface SWIP area into environmental provinces (EPs), evaluating their spatio-temporal distribution and abiotic properties, as well as the biological relevance of the partition. An unsupervised classification was based on nearly 10 years (2002–2011) of satellite- and model-derived data representative of physical, chemical and optical surface environments. Twelve EPs (two coastal, two slope and eight oceanic) presented areal coverage varying along the annual cycle with patterns significantly related to phytoplankton abundance and productivity. Highly significant intra-annual variability in province-specific area coverage and distinctions in the abiotic properties distinguished EPs predominant during cold (autumn–winter) and warm (spring–summer) periods. Areal coverage and abiotic properties of EPs predominant during the cold period presented higher variability in comparison to warm period EPs. During the warm period, the signature of coastal upwelling was evident, particularly over the western slope and coastal EPs. Riverine discharge was also a relevant local control of abiotic properties over coastal EPs. Overall, the spatio-temporal coverage patterns of EPs and abiotic and biotic properties showed a good agreement with previous studies of the SWIP area, particularly along the oceanic and slope sectors. The combination of a broad dataset, derived from products available through operational oceanography programs, and objective unsupervised data classification methods, represented a suitable strategy for characterizing SWIP ocean surface environment. Direct applications of this partition include its use as support for designing sampling strategies, ocean modelling, interpreting environmental and biological patterns, and ecosystem-based management.